Novos registros de Ceratopogonidae (Diptera) na região de Santa Maria, RS, Brasil - Lignon, Julia Somavilla (2022)
The Ceratopogonidae dipterans are small insects known by different names, but mainly as "maruins" or "mosquitos pólvora". Several species have medical and veterinary importance, causing great discomfort due to painful bites that can cause allergic reactions as well as being responsible for the transmission of various protozoa, filarial nematodes and viruses. Despite the knowledge about this importance, studies with these dipterans worldwide are still considered limited. Veterinary ectoparasites cause great losses in animal production, therefore, identifying possible disease vectors is of great epidemiological importance. The objective of this work was to survey the species of Ceratopogonids that occur in Santa Maria, Rio Grande do Sul, and verify the frequency of occurrence of adults within one year of capture. For this purpose, adult maruins were collected weekly (three nights a week) with a Captor® suction light trap, from March 2020 to March 2021, installed about 1.5 m above ground level in the peridomicile of rural property located in Santa Maria, RS. The collections were carried out between 6 p.m. and 6 a.m. and the specimens were separated from other insects and into morphospecies according to the wing pattern, for taxonomic identification at the species level. A total of 16,054 specimens (71.55% female to 28.44% male) of Ceratopogonidae were collected and identified, comprising thirteen species, with Culicoides insignis and Culicoides venezuelensis being the most abundant species. The data presented show that several species of Ceratopogonidae, including seven new records, occur in a rural property in Santa Maria, RS. It can be concluded from the data presented that several species of Ceratopogonidae, including seven new records, occur in a rural property in Santa Maria, RS. The maruins have variable frequency and occur throughout the year at the study site, with the largest number being in the warm season, regardless of sex. The most frequently collected species were C. insignis and C. venezuelensis. The present work highlights the lack of research and information regarding Ceratopogonidae in the state of Rio Grande do Sul, and although the study was carried out in a single location and with only one trap, a great diversity of species was obtained, suggesting that the real diversity in the state may be even greater. Furthermore, this is the first study using the Captor® suction light trap, which can be considered an efficient alternative, easy to handle and transport, and cheaper when compared to the CDC-type light trap, often used in entomological research.